(untitled) (Agroindustria, Sociedad y Ambiente, 2022)
The world and societies have evolved, the fourth industrial revolution has changed the perspective, even the way of doing activities. This carries over to organizational development. The application of specific skills are important within organizations, but transversal skills have taken on a certain role in the digital age. The use of information and communication technologies, change management, negotiation, conflict resolution and intelligent management of emotions must be taken into consideration in the management of the organization. The balance of conceptual, technical and human skills points to the achievement of the strategic objectives of the organization. For this reason, organizations must incorporate the development of all these skills into their strategic plan model in order to adapt to the new times.